2021
DOI: 10.3389/ffgc.2021.710854
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Alters Temperate Forest Canopies and Indirectly Reshapes Arthropod Communities

Abstract: Global change challenges the adaptive potential of forests. Large-scale alterations of forest canopies have been reported across Europe, and further modifications are expected in response to the predicted changes in drought and windstorm regimes. Since forest canopies are dynamic interfaces between atmosphere and land surface, communities of canopy-dwelling insects are at the forefront of major changes in response to both direct and indirect effects of climate change. First, we briefly introduce the factors sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…Anderegg et al 2013;McDowell et al 2020;Sallé et al 2021). As expected, we showed that forest dieback had an overall positive effect on the taxonomic diversity of saproxylic beetles, at both local and landscape scales.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Anderegg et al 2013;McDowell et al 2020;Sallé et al 2021). As expected, we showed that forest dieback had an overall positive effect on the taxonomic diversity of saproxylic beetles, at both local and landscape scales.…”
supporting
confidence: 85%
“…Lately, several large drought-related dieback events have been reported (Sangüesa- Barreda et al 2015), and a further increase in drought-induced dieback and decline in terms of frequency, intensity and spatial extent is expected to arise (Allen et al 2010;Samaniego et al 2018). As a consequence, deadwood supply and the number of tree-related microhabitats are likely to increase and this may favour saproxylic communities Thorn et al 2017;Sallé et al , 2021Cours et al 2021). Several local-scale (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite many decades of intense canopy research, there remain substantial gaps in our knowledge of the biodiversity and ecological interactions of canopy communities (Nakamura et al, 2017). This includes both tropical rainforests with their vast array of undescribed species (Basset et al, 2012), and temperate forests (Sallé et al, 2021). The degradation and loss of forests are accelerating in many regions of the world due to global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite many decades of intense canopy research, there remain substantial gaps in our knowledge of the biodiversity and ecological interactions of canopy communities (Nakamura et al, 2017). This includes both tropical rainforests with their vast array of undescribed species (Basset et al, 2012), and temperate forests (Sallé et al, 2021). The degradation and loss of forests is accelerating in many regions of the world due to global climate change.…”
Section: Introductionmentioning
confidence: 99%